Hybrid vertical graphene/lithium titanate–CNTs arrays for lithium ion storage with extraordinary performance. Issue 19 (4th May 2017) - Yao, Zhujun; Xia, Xinhui; Zhong, Yu; Wang, Yadong; Zhang, Bowei; Xie, Dong; Wang, Xiuli; Tu, Jiangping; Huang, Yizhong
Abstract : In the present study, we report a synthetic strategy for the direct fabrication of hybrid vertical graphene/lithium titanate–CNTs arrays via atomic layer deposition in combination with chemical vapor deposition. Abstract : In the present study, we report a synthetic strategy for the direct fabrication of hybrid vertical graphene/lithium titanate–CNTs arrays via atomic layer deposition in combination with chemical vapor deposition. A novel array architecture was formed where active lithium titanate (Li4 Ti5 O12, LTO) was uniformly sandwiched by a vertical graphene backbone and an interconnected CNTs shell. The hybrid omnibearing conductive network was identified to be an extremely stable porous structure and demonstrated superior ultra-high rate capability (146 mA h g −1 at 50C and 131 mA h g −1 at 100C) with a capacity of 136 mA h g −1 at 20C after 10 000 cycles when used as an electrode in lithium ion batteries. This special electrode construction strategy is expected to provide a new route for the manufacture of electrochemical energy storage with ultra-high rate capability and ultra-stability.